2010
DOI: 10.1021/ic100181d
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Control on the Formation of Two Novel Metal-Organic Frameworks Based on the Er(III) Ion and the Asymmetric Dimethylsuccinate Ligand

Abstract: Two new layered polymeric frameworks have been synthesized under different hydrothermal conditions and characterized by single-crystal X-ray diffraction, thermal analysis, and variable temperature-Fourier Transform Infrared Spectroscopy (VT-FTIR). The compound I, with formula [Er(2)(dms)(3)(H(2)O)(4)], has a triclinic cell with parameters a = 5.8506 A, b = 9.8019 A, c = 11.9747 A, alpha = 70.145 degrees , beta = 80.234 degrees , and gamma = 89.715 degrees , and the compound II, [Er(2)(dms)(3)(H(2)O)], is monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 54 publications
(43 reference statements)
2
37
0
Order By: Relevance
“…The inorganic chains are linked by two crystallographic independent succinate anions resulting in a 2D organic‐inorganic framework. H‐bonds involving hydration and coordination water molecules along with oxygen atoms from carboxylate groups ensure the packing.2D‐3 structural type was reported for erbium, yttrium and lutetium frameworks based on the 2,2‐dms ligand. Different space groups (S.G.) were reported, P 1 being for the erbium compound, and P ī for the yttrium and lutetium ones.…”
Section: Structural and Topological Revisionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inorganic chains are linked by two crystallographic independent succinate anions resulting in a 2D organic‐inorganic framework. H‐bonds involving hydration and coordination water molecules along with oxygen atoms from carboxylate groups ensure the packing.2D‐3 structural type was reported for erbium, yttrium and lutetium frameworks based on the 2,2‐dms ligand. Different space groups (S.G.) were reported, P 1 being for the erbium compound, and P ī for the yttrium and lutetium ones.…”
Section: Structural and Topological Revisionmentioning
confidence: 99%
“…Different space groups (S.G.) were reported, P 1 being for the erbium compound, and P ī for the yttrium and lutetium ones. In the case of the Er 3+ framework, to rule out the centrosymmetric space group and the existence of a non‐resolvable positional disorder, the structure was solved in the P 1 S.G., where the occupation factors of the methyl groups of the trans dms anion were equal to 1. If such disorder would exist, the occupation factors of these methyl groups should have been 1/2 also in the P 1 S.G.…”
Section: Structural and Topological Revisionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that this ligand tend to construct polynuclear coordination polymers, meanwhile, the polymers based on this ligand have been less explored, [17][18][19][20][21] and (3) …”
Section: Introductionmentioning
confidence: 99%
“…The complexes can be obtained by the reactions of the same ligand with the same center metal via controlling synthetic conditions such as counterions, pH value, reaction solvent, and the ratio of metal/ligand [22][23][24][25][26]. In this paper, we obtained two 3D supramolecular coordination polymers from 1D structure via controlling Electronic supplementary material The online version of this article (doi:10.1007/s10904-015-0237-y) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%